2019
DOI: 10.1111/ffe.13078
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of metal‐composite adhesive joints under debonding modes I, II, and I/II using the results of experimental and FEM analyses

Abstract: In the present study, the experimental and finite element (FE) analyses are first carried out to investigate the deboning behavior of metal‐composite adhesive joints under modes of I and mode II loading. To conduct an FE on the debonding propagation, cohesive zone method (CZM), as well as maximum nominal stress and energy criteria, is applied. In the reliability analysis, to achieve the probability of debonding growth (PODG), limit state functions are formulated based on the energy release rate. To that end, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…An in-depth finite element analysis on Mode-I and mixed-mode I/II by Zhao et al [ 14 ] found that the interface strength of composite laminates within a certain boundary has minuscule effects on the simulation results. This insignificant effect of interface strength is also stated by Delbariani et al [ 15 ] in their study of metal–composite joints. Tsokanas and Loutas [ 16 ] expressed the complications in analytical modelling of dissimilar materials due to disparate ductility and thermal behaviour which have substantial effects on delamination properties.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…An in-depth finite element analysis on Mode-I and mixed-mode I/II by Zhao et al [ 14 ] found that the interface strength of composite laminates within a certain boundary has minuscule effects on the simulation results. This insignificant effect of interface strength is also stated by Delbariani et al [ 15 ] in their study of metal–composite joints. Tsokanas and Loutas [ 16 ] expressed the complications in analytical modelling of dissimilar materials due to disparate ductility and thermal behaviour which have substantial effects on delamination properties.…”
Section: Introductionsupporting
confidence: 69%
“…Mode-I and Mode-II delamination properties at each temperature[27,28]. 15. 12.47 ± 0.46 7.25 ± 0.08 239.97 ± 7.10 134.50 ± 1.91 91.97 ± 2.59 FP (N) 34.51 ± 2.42 22.04 ± 1.23 10.55 ± 0.16 297.3 ± 4.63…”
mentioning
confidence: 99%
“…[208] Alternatively, a model-based characterization of the stress state is also possible . [198,[209][210][211] For example, the analytical model by Volkersen was considered in [198] to quantify the shear stress inside the adhesive in composite-aluminium patches with randomly varying adhesive thickness. The maximum shear stress was then extracted from the numerical solution of the model and inserted in equation 17 as representative measure of the stress driving the occurrence of failure in the adhesive joint.…”
Section: Probabilistic Methodsmentioning
confidence: 99%
“…VCCT and CZM show advantages in different aspects; therefore, in recent years, more and more researches are more inclined to use the method of combining both the models. [32][33][34] Many studies nowadays are based on the delamination failure calculation of DCB, ELS, or other similar simple standard tests, with uniform thickness and straight delamination front edge, [35][36][37][38] and few studies were made on the delamination process of non-uniform materials. Shokrieh et al 35 studied the influence of curved delamination front on toughness of multidirectional DCB specimens and established a methodology to predict the maximum delamination toughness (G Imax ) of multidirectional DCB specimens without performing any experiments.…”
Section: Introductionmentioning
confidence: 99%